Molecular Identification and Phylogenetic Analysis of Ascarids in Wild Animals - Chen, Shu-Yu; Qiu, Qi-Guan; Mo, Hai-Long; Gong, Teng-Fang; Li, Fen; He, Jun-Lin; Li, Wen-Chao; Xie, Xin-Rui; Liu, Wei (Frontiers in Veterinary Science, 2022)
Ascarid worms are common nematode parasites that cause a serious hazard in many animal species and posing an important zoonotic concern. This study explores the genetic and phylogenetic relationship among ascarids from 11 different hosts by analyzing genetic variation. This study collected ascarid samples from the feces of nine animal species in Changsha Ecological Zoo of Hunan Province and two animal kinds in the College of Veterinary Medicine of Hunan Agricultural University. The mitochondrial gene (pcox1) and ribosomal ITS sequences were amplified, sequenced, and analyzed by PCR to identify the species of the samples. The phylogenetic tree was constructed based on two genes (cox1 and ITS) by the Neighbor-joining method, and the phylogenetic relationship was analyzed. The sequencing results showed that the sequence lengths of pcox1 and ITS genes in the samples were 441 bp and 838 ~ 1177 bp, respectively. The difference rates were 0.00% ~ 1.70% in pcox1 gene and 0.00% ~ 7.30% in ITS gene. Phylogenetic analysis showed that ascarid worms from the white lion, Northeast tiger, South China tiger and cheetah were identified as Toxascaris leonina. Ascarids from the zebra was identified as Parascaris equorum, while those from chicken and peacocks were identified as Ascaridia galli. Ascarids of wolf and dog origin were Toxocara canis, the snake ascarids belonged to Ophidascaris filaria, and the bear ascarids belonged to Baylisascaris transfuga. There was a significant gap between different kinds of ascarid worms. Using both genes (pcox1 and ITS), the intraspecific differences were significantly smaller than the interspecific differences, suggesting that these two genes could be used as interspecific genetic markers for molecular identification of ascarids from different origins. The intraspecific variation rate of ITS gene was higher than that of pcox1, indicating that ITS can also be used in the genetic research of ascaris species development. This study revealed the genetic evolution and phylogeny of ascarids in wild animals, would help in the prevention and control of ascarids in wild animals.